Numerical solution of nonlinear fredholm and volterra integrals by Newton–Kantorovich and Haar wavelets methods - Mohammad Hasan, Abdul Sathar; Ahmad Fadly Nurullah, Rasedee; Ahmedov, Anvarjon A.; Norfifah, Bachok (MDPI AG, 2020)
The current study proposes a numerical method which solves nonlinear Fredholm and Volterra integral of the second kind using a combination of a Newton–Kantorovich and Haar wavelet. Error analysis for the Holder classes was established to ensure convergence of the Haar wavelets. Numerical examples will illustrate the accuracy and simplicity of Newton–Kantorovich and Haar wavelets. Numerical results of the current method were then compared with previous well-established methods.